Historical and Diplomatic Linkages between Nigeria and Fernando Po (Bioko Island), Equatorial Guinea Since 1968 - Preye Adekoya; Thaddeus T. Ityonzughul (Universitas Medan Area, 2026)
This study explores the historical and diplomatic ties between Nigeria and Fernando Po (Bioko Island, Equatorial Guinea) since 1960. However, references are made to the periods preceeding the era to established historical links. The analysis touches pre-colonial trading networks, colonial partitioning, and current nautical and economic contacts. The study explores how historical ties and economic imperatives have influenced Nigeria-Equatorial Guinea relations, particularly regarding maritime border disputes and oil exploitation. Using qualitative research methods, the analysis emphasises the long-lasting legacy of colonial borders, the importance of regional organisations such as ECOWAS, and the significance of oil discoveries on bilateral negotiations. The paper reveals that, while shared ethnic and cultural links serve as a foundation for cooperation, opposing economic interests, particularly over offshore oil deposits, have caused recurring conflicts, resulting in diplomatic talks and occasional conflict. It concludes that Nigeria-Fernando Po relations present both challenges and opportunities. This study adds to the discussion of post-colonial state formation, resource diplomacy, and regional integration in West Central Africa by combining historical and contemporary perspectives.